Early application of the Ponseti casting technique for clubfoot correction in sick infants at the neonatal intensive care unit. Issue 2 (March 2017) - Lebel, Ehud; Weinberg, Eliraz; Berenstein-Weyel, Tamar M.; Bromiker, Ruben
Abstract : The treatment of congenital clubfoot has been changing rapidly since the mid-1990s with the worldwide use of the Ponseti method for serial casting and limited operative interventions. This method was first applied for isolated clubfeet and later on for other types of clubfoot (teratologic, residual, and neurogenic). Premature babies sustaining clubfoot commonly suffer from additional congenital and acquired medical problems. These may postpone clubfoot management until urgent issues are resolved. The current study describes early initiation of treatment of clubfoot in premature babies at the neonatal intensive care unit (NICU) and their outcomes. The study group included all babies diagnosed with clubfoot and managed in the NICU (for any etiology) between 2006 and 2012. Management was based on the Ponseti protocol for serial casting. We also report on neonates who died in the NICU before or during treatment. We specifically describe adverse events of early casting and situations necessitating removal of casts or termination of treatment. We diagnosed and treated 20 neonates with clubfoot (four females and 16 males, 10 bilateral cases). Gestational age ranged from 27 weeks to term. Eight were identified with clubfoot by prenatal sonographic survey and 10 were diagnosed with a defined syndrome. Seven had respiratory support, including one with a chest drain (50%). Length of stay in the NICU ranged from 3 to 90 days. Four neonates died while in the NICU (all syndromatic). In the remaining 16 cases, treatment began as early as medically possible. The first cast was applied within the first week of life in 14 cases. A total of 75 casts were applied during the study period. Three casts (4%) were removed because of leg edema or a need for venous access. Casts were routinely replaced every 4–7 days. Achilles tenotomies were performed in the NICU for babies achieving satisfactory correction. At last follow-up, 10 children were independent walkers and six were nonambulatory; all showed successful correction of clubfeet. The results of this study show that in most cases, clubfoot treatment is feasible and effective within the first week of life. Instances necessitating immediate cast removal are highlighted. Although while facing acute life-threatening medical problems, the treatment of clubfoot may not be considered a priority, most neonates will grow up into independent individuals; thus, every effort should be made to initiate the best clubfoot management with minimal delay.